A COVID-19 Patient Presenting with Pneumothorax. (16th April 2021) - Abootalebi, Seyyedeh Narjes; Shorafa, Eslam; Abbaspour, Alireza; Dehghani, Seyed Sina; Forooghi, Mehdi
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel virus that has affected millions of individuals across the world. It was officially declared as a pandemic on March 11, 2020. Although most patients with COVID-19 manifest as viral pneumonia characterized by symptoms such as fever, dyspnea, and cough, atypical presentations such as acute respiratory distress syndrome (ARDS) and acute kidney or cardiac injury have been reported amongst COVID-19 patients. Bilateral and peripheral ground-glass and opacities are the hallmarks of COVID-19 infection on imaging exams. Herein, we aim to describe a COVID-19 patient who presented with shortness of breath, neck pain, chest pain, and bilateral pneumothorax in his imaging exam.